Social security reforms in Kenya: Towards a workeristor a citizenship-based system? - Künzler, Daniel (University of Fribourg, Department of Social Sciences, Switzerland, 2016)
With social security provisions in Kenya remainingunder-reported in the more recent literature, this overviewcovers recent reforms in key areas of the country’ s social secu-rity system. In the health sector and in old-age pension provi-sion social security is still mainly workerist (biased towardthose in formal employment), and attempts to expand cove-rage have had limited effect only – cash transfer programmes,for instance, have been expanded but in practice they do notuniversally cover the entitled categories. Thus, although theKenyan social security system now has a considerable pro-poor social assistance component it remains biased towardthose in formal employment, to the beneﬁt of the highest in-come quintile.
full text
Keywords: coverage, social policy, provident fund, socialinsurance, social assistance, Kenya, Africa